Effect of Exopolysaccharide-Producing Bacteria on Water-Stable Macro-Aggregate Formation in Soil. Issue 8 (13th July 2020) - Cheng, Cheng; Shang-Guan, Wangli; He, Linyan; Sheng, Xiafang
Abstract: Microorganisms play an important role in soil aggregate formation; however, little is known concerning the impact of exopolysaccharide (EPS)-producing bacteria on water-stable soil macro-aggregate formation. In this study, a forest soil was collected and used for the isolation of EPS-producing Pseudomonas chlororaphis A20 and Bacillus proteolyticus A27. The isolation and purification of the EPS were made. Then, the strains and their EPS were investigated for their impact on water-stable soil macro-aggregate formation. Xylose and aldohexos were found in the EPS produced by these strains, whereas the EPS of strain A27 also contained rhamnose and glucose. The EPS of these strains demonstrated distinct Fourier transform-infrared spectrums. These strains increased the ratio of water-stable macro-aggregates (>0.25 mm) by 128–169%, polysaccharide content by 158–174%, and invertase activity by 153–193% in the soils compared with the controls. Strain A27 induced more water-stable soil macro-aggregates and higher invertase activity than strain A20. Furthermore, the EPS of strain A27 increased the ratio of water-stable macro-aggregates by 10–36% compared to that of strain A20. The results showed distinct bacterial impact on the water-stable macro-aggregate formation and suggested that higher bacterial activity and specific EPS of strain A27 may be responsible for increased water-stable soil macro-aggregate formation.